Assessing the logistics activities aspect of economic and social development - (:unkn) unknown (Inderscience Publishers, 2018)
Logistics is concerned with the coordination and planning of products, services and information flow between the points of production and consumption. The logistics sector, contributes directly to production and consumption activities, has a critical importance for social and economic development. In this study, Turkey’s logistics map was created in order to distribute the logistics burden in the cities which have intensive logistics activities and improve logistics ability in the cities which have poor logistics activities. Firstly, social and economic variables that affect the logistics operations of cities of Turkey were investigated. The identified variables were reduced to a single factor which is called logistics via factor analysis and the clustering analysis was performed by using the logistics factor. In clustering analysis, k-means method was used and the cities of Turkey clustered from strong to weak according to logistics activities. The obtained results were analysed and interpreted. Copyright © 2018 Inderscience Enterprises Ltd.
Keywords: Clustering; Factor analysis; Logistics; Turkey